AMIA Advocates National Health Information System in Fight Against National Health Threats - Tang, Paul C. (American Medical Informatics Association, 2002)
To protect public health and national safety, AMIA recommends that the federal government dedicate technologic resources and medical informatics expertise to create a national health information infrastructure (NHII). An NHII provides the underlying information utility that connects local health providers and health officials through high-speed networks to national data systems necessary to detect and track global threats to public health. AMIA strongly recommends the accelerated development and wide-scale deployment of electronic public health surveillance systems, computer-based patient records, and disaster-response information technologies. Such efforts hold the greatest potential to protect our citizens from disaster and to deliver the best health care if disaster strikes.